Feasibility Study of Odo River Water Tourism Business in Gedangan Tuntang Village, Semarang Regency - Finata, Chandra; Utama, Tri Surya; Febriani, Aglia; Sakti, Imanuel Madea (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This study aims to determine the extent to which the development of Odo River water tourism in Gedangan Tuntang Village, Semarang Regency. The development of this tourism is based on data from interviews with the head of the water tourism management and the distribution of questionnaires to visitors to the water tourism. In this analysis using technical aspects, environmental aspects and marketing aspects. Through data collection that has been done, there are potentials that can be developed. Through the technical aspects of developing a culinary kiosk arrangement, it can increase visitor comfort, adding water rides so that visitors are more interested, arranging parking lots and making toilets to support existing facilities. The environmental aspect is an aspect that has a very high risk because of that waste management in Kali Odo tourism is very much considered by making storage tanks and providing trash cans in every corner. The development of Odo River Water Tourism in Gedangan Tuntang Village, Semarang Regency can be said to be realized if all these aspects can be fulfilled properly.